Long-distance moves and labour market outcomes of dual-earner couples in the UK and Germany - Philipp M. Lersch (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Chances are high that partners in dual-earner couples do not receive equal occupational returns from long-distance moves, because job opportunities are distributed heterogeneously in space. Which partners are more likely to receive relatively higher returns after moves? Recent research shows the stratification of returns by gender and highlights the importance of gender roles in mobility decisions. I extend past literature in two ways. First, while past research mostly examined partners separately, I directly test for gender differences in matched pairs of women and men in dual-earner couples and account for the nonindependence of both careers. Second, I compare evidence from the United Kingdom (UK) and Germany to shed light on the effects of institutional and normative contexts. For my analysis, I draw longitudinal data from the British Household Panel Survey and the German Socio-Economic Panel Study (1991-2008). My results show that women in dual-earner couples are temporarily adversely affected in their careers by long-distance moves in the UK and West Germany after controlling for various characteristics of both partners. Women in East Germany are not affected by long-distance moves. Moves do not change wage rates significantly for women and men that stay in employment in both countries.
Keywords: 330; residential mobility; gender inequalities; cross-national comparison; actor-partner interdependence model